Youth and the pandemic: health information imaginaries and practices while navigating COVID-19 in Nigeria - Uzuegbunam, Chikezie E. (Frontiers in Communication, 2025)
This study explores young adults’ perceptions, behaviors, and how they navigated pandemic-related information, drawing from social cognitive theory. In the digital age, young people, characterized as “digital informavores,” actively seek, consume, and share information, playing a crucial role in health communication. The research, involving participants aged 18–30 in two urban centers in Nigeria, focused on COVID-19 socio-health concerns, including social distancing, masking, sanitizing, movement restrictions, vaccination, infection, testing, and treatment. The analysis, employing the social cognitive lens, and following a critical thematic approach, indicates that the degree of infodemic exposure experienced during the pandemic impacted participants’ understanding, attitudes, behaviors, and risk perceptions. Participants primarily relied on digital sources and social support systems for pandemic-related health information. Their self-efficacy and risk perceptions, as well as pandemic-induced affectations, were evident throughout the data. Attitudes toward the pandemic evolved from its onset, through the announcement and easing of the national lockdown, to the vaccination rollout. Dominant perceptions included the use of “copy and paste solutions” in Nigeria’s pandemic response, COVID-19 denialism, and politicization of the pandemic, leading to mistrust in government and health authorities. The pandemic’s impacts included mental health issues and economic hardship, particularly in a country lacking social security or welfare plans. Following a low vaccination rate among participants, the data revealed vaccine lethargy, “vaccinformation void,” vaccine misinformation, vaccine distrust, and vaccine inaccessibility, due to various reasons and factors at play. Some young adults adhered to health rules due to fear and anxiety, while others were nonchalant, overwhelmed by the rules or discouraged by others’ non-compliance. The young adults’ imaginaries and behaviors were influenced by sociocultural intermediaries, religious and political actors, and Nigeria’s socio-economic conditions.